Nearshore Areas Used by Fry Chinook Salmon, Oncorhynchus tshawytscha, in the Northwestern Sacramento–San Joaquin Delta, California - Jeff McLain; Gonzalo Castillo (San Francisco Estuary and Watershed Science, 2010)
We reported the geographic distribution and the densities and catch rates of fry Chinook salmon, Oncorhynchus tshawytscha, found in different substrata and nearshore zones in the northwestern Sacramento-San Joaquin Delta of the San Francisco Estuary, California, USA. Nearshore zones in the fresh-water, tidally influenced northwest delta were dominated by riprap, and contained sparse sections of tule beds, beaches, and riparian zones. A total of six beach seine sites and eight electrofish sites were sampled during winter 2001 along the Sacramento River, Steamboat Slough, Miner Slough, Prospect Island Marsh, Prospect Slough, and Liberty Island Marsh. Overall, fry densities were higher on the Sacramento River and Steamboat Slough and lower in Liberty and Prospect Island marshes. Chinook salmon fry were significantly larger in the Sacramento River than in Steamboat Slough during March. Highest densities of Chinook salmon fry were observed in shallow beaches than in riprap nearshore zones. Fry densities also increased with Secchi depth and richness of non-native predators, suggesting increased predation risk by opportunistic predators. Shallow nearshore environments in conveyance channels, such as Steamboat Slough and the Sacramento River, seem important for Chinook salmon fry rearing. Conversely, riprap in these channels could reduce fry rearing habitat. Although fry catch rates by electrofishing did not differ greatly among riparian, riprap, beach and tule nearshore zones, they were on average about one-third higher in beaches. Evaluating potential impacts of habitat quality on growth and survival of fry seems key to further assess and monitor restoration efforts in the delta.